Cardiovascular outcomes in long COVID-19: a systematic review and meta-analysis - Ting Zhang; Zhimao Li; Qimin Mei; Joseph Harold Walline; Zhaocai Zhang; Yecheng Liu; Huadong Zhu; Bin Du (Frontiers in Cardiovascular Medicine)
IntroductionThere is growing evidence that patients with SARS-CoV-2 (The severe acute respiratory syndrome coronavirus 2) may have a variety of cardiovascular complications in the post-acute phase of COVID-19, but these manifestations have not yet been comprehensively characterized.MethodsWe performed a systematic review and meta-analysis of primary research papers which evaluated individuals at least four weeks after confirmed COVID-19 diagnosis and reported on cardiovascular disease prevalence. Systematic search conducted without language restrictions from December 1, 2019 to June 31, 2022 on PubMed, EMBASE, Web of Science, Cochrane library, ProQuest Coronavirus Research Database, COVID-19 Living Overview of the Evidence (L-OVE) subset of Episteminokos and the World Health Organization (WHO) Covid-19 databases. Study was reported according to MOOSE-lists and the PRISMA guidelines. The risk of bias was identified using the Newcastle-Ottawa Scale (NOS) for observational studies. Random-effects meta-analyses examined the pooled risk difference in the prevalence of each symptom or symptom combination in cases with confirmed SARS-coV-2 infection compared with controls.ResultsEight cohort studies were eligible, including nearly 10 million people. Long COVID-19 was associated with a higher risk of thromboembolic disorders [HR 3.12 (1.60, 6.08)], coronary heart disease [HR 1.61 (1.13, 2.31)], stroke [HR 1.71 (1.07,2.72)], arrhythmia [HR 1.60 (1.13, 2.26)], cardiomyopathy [HR 1.71 (1.12, 2.61)], myocarditis [HR 6.11 (4.17,8.94)], hypertension [HR 1.70 (1.56, 1.85)], heart failure [HR 1.72 (1.15,2.59)] and cardiogenic shock [HR 2.09 (1.53,2.86)] compared to non-COVID-19 controls. Pooled risk differences in long COVID cases compared to controls were significantly higher for cardiomyopathy [0.15% (0.06, 0.23)], deep vein thrombosis [0.45% (0.06, 0.83)] and hypertension (0.32%, (0.06, 0.58) but not for thromboembolic disorders, coronary disease, stroke, arrhythmia, cardiomyopathy, myocarditis, hypertension, heart failure or cardiogenic shock.ConclusionThe risk of cardiovascular disease increased significantly four weeks or more after recovering from acute COVID-19. Care for survivors after an acute attack of COVID-19 should include paying close attention to cardiovascular health and disease.Systematic Review RegistrationPROSPERO [CRD42022353965].